(untitled) (Comillas Journal of International Relations, 2022)
After a year of deliberations, the final report of the CoFoE (2022) collected almost fifty proposals and more than three hundred measures. The initiative was conceived as an inclusive platform to collect different voices and offer spaces in which European citizens could express themselves. In addition, it sought to underpin the democratic legitimacy and the future of the European project. After a process with hits and misses, it is now up to the European institutions to take charge. That is, to take a step towards the politicization of the EU by implementing the proposals put forward by the Conference and establishing permanent channels of participation and deliberation, thus promoting the European public sphere, and allowing the “institution of dissent” or politicization to take the place of the “institution of consensus”; or, on the contrary, ignore citizen demands. The future of Europe may depend on it.